PROGRESS FROM SELECTION OF SOME MAIZE CULTIVARS’ RESPONSE TO DROUGHT IN THE DERIVED SAVANNA OF NIGERIA - O. J. Olawuyi; O.B. Bello; C. V. Ntube; A. O. Akanmu (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
Field experiments were conducted to investigate the variations in sixteen maize genotypes in relation to drought tolerance. The experimental set up was subjected to drought stress after five weeks of planting for three weeks before data on morphological and yield characters of maize genotypes were [DBO1] obtained for three cropping years. Plant height and grain yield of Bodija yellow maize were the highest overall. There was a significant difference among genotypes for drought stress resistance and Bodija yellow maize showed the most tolerance, while TZBR Comp 1 – C1 S2 510 genotype was the least. First principal component axis (Prin 1) had the highest contribution to the variation of the morphological, yield and drought tolerance traits. Prin 1 was highly related to the morphological and yield characters more than to the drought resistance. [U2] Plant height was negatively and strongly correlated (p<0.01) with stem height, number of leaves, stem girth, leaf length, leaf width and week after planting, but negatively correlated with the drought resistance. Therefore, Bodija yellow maize should be considered as parent material in breeding for the development of drought tolerant traits in maize.